How American-based Television Commercials Portray Convicts, Correctional Officials, Carceral Institutions, and the Prison Experience. Issue 2 (3rd April 2018) - Ross, Jeffrey Ian; Sneed, Vickie
ABSTRACT: The manner in which deviant and marginalized groups are portrayed in popular culture shapes public perceptions and policy responses. These messages are communicated through a variety of channels. Over the past decade, scholarly interest in the portrayal of prisoners, correctional officers, and correctional institutions has increased. One of the unexplored, important, and relatively contemporary mediums through which inmates, correctional officers, and carceral spaces have been portrayed is through commercials. These messages appear via print, television, and the Internet. In an attempt to understand the content and context of these commercials, the following article presents the results of a content analysis of American-based television commercials that feature convicts, correction officials, prison settings, and/or the carceral experience.